Soil Moisture - Civeira, Gabriela (IntechOpen, 2019)
This book is aimed at the majority of audiences who need to rapidly obtain a concise overview of soil moisture measurement and management. Many existing soil moisture textbooks cater for a traditional market where readers rely on years of study presented in a slender discipline. The evolution of segmental schemes has meant that soil moisture is now often included as a part of broad-based soil science programs. For those opting to specialise in soil moisture, this is a good book to choose. This book will be very useful to students, researchers and other readers who do not hold a traditional scientific background, such as those studying geography, environment science, ecology and agriculture. This book provides a concise overview of soil moisture knowledge.